Pap Smear Test as Screening Tool for the Prevention of Carcinoma Cervix: An Institutional Study - Sinha, Riti Tushar Kanti (Annals of Pathology and Laboratory Medicine, 2020)
Background: Cervical cancer has become the leading cause for mortality in women worldwide, especially indeveloping countries, estimated to be the fourth common cancer among women. Present study was done with an aim to observe the effectiveness of Pap Smear Screening for detection of precursor pre cancerous lesions of the cervix and Prevention of Cervical Cancer at Kolkata, India. Methods: The present study is a retrospective study done in the department of Pathology ESI-PGIMSR, Medical College and Hospital, Joka, Kolkata for a period of one year. The smears were taken with sterile Ayer’s spatula. Both ectocervix and endocervix were sampled. Materials were smeared on a pre-labelled glass slides to form a monolayer thick smear. Slides were fixed with methanol, which after drying were stained by rapid pap method. The conventional smears were screened and reported according to The Bethesda system 2001. Results: Out of total 110 smears, inflammatory smear was the most common abnormality Other lesions like Low grade squamous intraepithelial lesion (LSIL), High grade squamous intraepithelial lesion (HSIL) and Atypical squamous cells of undeterrmined significance (ASCUS) were observed. Age group between 41-50 years contributed highest number of cases followed by age group between 31-40 years. Conclusion: Pap smear testing is a very useful, simple, economical, and safe tool for detecting precancerous lesions of the cervix . The Pap test has been regarded as the gold standard of cervical screening programs Countries like India with predominant rural population having low socio-economic status, marriage atan early age and poor medical facility , it is a major challenge to formulate a screening program that is easily available, within existing resources, to a large section of society.